2019
DOI: 10.1111/head.13630
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis Following Discontinuation of OnabotulinumA Therapy in “Super‐responding” Chronic Migraine Patients

Abstract: Objective To determine whether the successful treatment of chronic migraine (CM) with onabotulinumA (BotoxA) may be followed by a continued respite from headache once therapy has been discontinued. Background The optimal duration of prophylactic therapy for migraine generally and for CM treated with BotoxA specifically is unknown. Methods We conducted a prospective cohort study evaluating a series of patients with CM at a university‐affiliated headache subspecialty clinic in Reno, Nevada, all of whom were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
1
14
0
2
Order By: Relevance
“…However, previous research on self‐reported wear‐off over ≥2 cycles suggested that ~20% of the patients experience repetitive wear‐off 17 . On the contrary, it has been reported that injections may successfully be delayed without exacerbation of headache in some patients, especially after the first year of treatment 27,28 . Reducing injection intervals to less than 12 weeks would be a possible strategy to counteract wear‐off in selected patients with repeated wear‐off.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research on self‐reported wear‐off over ≥2 cycles suggested that ~20% of the patients experience repetitive wear‐off 17 . On the contrary, it has been reported that injections may successfully be delayed without exacerbation of headache in some patients, especially after the first year of treatment 27,28 . Reducing injection intervals to less than 12 weeks would be a possible strategy to counteract wear‐off in selected patients with repeated wear‐off.…”
Section: Discussionmentioning
confidence: 99%
“…In one prospective study, 49% of a cohort of 276 patients were withdrawn from OnaB-A after meeting the predefined criteria fewer than five MHD for two consecutive 12-week cycles and a MIDAS score of <10. Over six-months of follow-up, 80% of patients had no clinical worsening or need to resume preventative treatment [76]. In a smaller case series, OnaB-A was withdrawn in 54 patients who reverted to an episodic pattern, of whom 80% remained episodic migraine after six months [76].…”
Section: Stopping Botulinum Toxinmentioning
confidence: 99%
“…On the contrary, Rothrock's group did not find, after 6 months, a worsening in migraine frequency in the group of "super-responders" to the BT-A, i.e., those patients achieving a migraine frequency and disability level for which prophylaxis is usually not indicated (16). The present study seems to confirm the results achieved by the first two ones (14,15), likely because of the higher rate of MOH sufferers in the analyzed sample if compared with the one of Rothrock's group (16). MOH increases CM patients' refractoriness to preventive treatments (3), and the analyzed sample was featured by a long CM history and a long MOH duration (Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, Guerzoni and collaborators found a general worsening of the patients' conditions (14), and, similarly, Cernuda-Morollòn and co-workers found out that 90% of patients reaching the year of treatment with the BT-A needed to continue it without delay to keep migraine frequency under control (15). On the contrary, Rothrock's group did not find, after 6 months, a worsening in migraine frequency in the group of "super-responders" to the BT-A, i.e., those patients achieving a migraine frequency and disability level for which prophylaxis is usually not indicated (16). The present study seems to confirm the results achieved by the first two ones (14,15), likely because of the higher rate of MOH sufferers in the analyzed sample if compared with the one of Rothrock's group (16).…”
Section: Discussionmentioning
confidence: 94%